(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2023)
In the educational system, this article offers information on how to use interactive ways of testing students’ knowledge of Microsoft Excel functions and formulae to increase the efficacy of the coursework. A teacher’s (pedagogue’s) ability to use express-test methods in place of other methods, the activation of students’ cognitive activity, and the integration of games and labor activities into the educational process are all imperative during practical training. Multidisciplinary modules are used in the educational process to structure learning and focus on developing general professional skills and the broad application of education.